COMPETENCE OF SOCIAL WORKERS IN DESIGNING CASE MANAGEMENT - Willya Achmad (Jurnal Ekonomi, 2023)
Case management is a crucial strategy within the field of social work that facilitates the resolution of social issues faced by both individuals and communities. The proficiency of social workers in formulating case management strategies is a crucial determinant of the efficacy of social interventions. The primary objective of this study is to examine and assess the proficiency of social workers in the development of case management strategies. This study employs a qualitative methodology, utilizing in-depth interviews and document analysis as data collection methods. The participants of this research are social workers who possess extensive expertise in several social settings. This study yields the conclusion that case management within the field of social work plays a significant role in delivering comprehensive assistance to individuals and families with intricate requirements. The case management process involves multiple stages that include outreach, needs assessment, service plan development, implementation, coordination, advocacy, reassessment, and case closure. Social workers must have strong competencies in communication, interpersonal skills, crisis intervention, and patient and family counseling to be successful in their work. Ethics and values are an important foundation in case management practice, and social workers must adhere to codes of ethics and professional guidelines. Additionally, they must be sensitive to cultural and linguistic differences and collaborate with various third parties involved in client care. With a deep understanding of a client's situation and appropriate skills, social workers can help individuals and families achieve greater well-being and overcome the challenges they face.